Caspase Activation and Aberrant Cell Growth in a p53+/+ Cell Line from a Li-Fraumeni Syndrome Family - Sherif, Zaki A. (Genetics Research International, 2015)
Wild-type p53 is well known to induce cell cycle arrest and apoptosis to block aberrant cell growth. However, p53’s unique role in apoptosis and cell proliferation in Li-Fraumeni Syndrome (LFS) has not been well elucidated. The aim of this study is to characterize the activity of wild-type p53 protein in LFS family dominated by a germline negative mutant p53. As expected, etoposide-treated wild-type p53-containing cell lines, LFS 2852 and control Jurkat, showed a greater rate of caspase- and annexin V-induced apoptotic cell death compared to the p53-mutant LFS 2673 cell line although mitochondrial and nuclear assays could not detect apoptosis in these organelles. The most intriguing part of the observation was the abnormal proliferation rate of the wild-type p53-containing cell line, which grew twice as fast as 2673 and Jurkat cells. This is important because apoptosis inducers acting through the mitochondrial death pathway are emerging as promising drugs against tumors where the role of p53 is not only to target gene regulation but also to block cell proliferation. This study casts a long shadow on the possible dysregulation of p53 mediators that enable cell proliferation. The deregulation of proliferation pathways represents an important anticancer therapeutic strategy for patients with the LFS phenotype.